Influence of patient isolation due to colonization with multidrug-resistant organisms on functional recovery after spinal cord injury - Prang, Peter; Schuld, Christian; Rupp, Rüdiger; Hensel, Cornelia; Weidner, Norbert (PLOS ONE, 2021)
Study design Chart reviews were combined with neurological and functional outcome data obtained from the prospective European Multicenter Study on Spinal Cord Injury (EMSCI, www.emsci.org). Objectives To determine if strict physical isolation of multidrug-resistant organisms (MDRO)-positive patients negatively affects neurological recovery and functional outcome in the first year after acute spinal cord injury (SCI). Setting SCI Center Heidelberg University Hospital. Methods Individuals with acute (< 6 weeks) traumatic or ischemic SCI were included. During primary comprehensive care, isolated MDRO-positive patients (n = 13) were compared with a MDRO-negative control group (n = 13) matched for functional (Spinal Cord Independence Measure-SCIM) and neurological impairment (motor scores based on the International Standards for Neurological Classification of Spinal Cord Injury—ISNCSCI) at an early stage up to 40 days after SCI. SCIM scores and motor scores were obtained at 12 weeks (intermediate stage) and 24 or 48 weeks (late stage) after SCI. Results Isolated MDRO-positive (median duration of hospitalization: 175 days, 39% of inpatient stay under isolation measures) and non-isolated MDRO-negative (median duration of hospitalization: 161 days) patients showed functional and neurological improvements, which were not statistically different between groups at the intermediate and late stage. Conclusion Prolonged isolation due to MDRO colonization for over a third of the inpatient comprehensive care period does not appear to impair neurological recovery and functional outcome within the first year after SCI.
Gesehen am 18.05.2021